(untitled) (Research, Society and Development, 2024)
Introduction: Inflammatory Bowel Disease (IBD) belongs to a group of chronic diseases, whose etiopathogenesis is still unclear, which affect the entire gastrointestinal tract (GIT). The main types of IBD are Crohn’s disease (CD) and Ulcerative Colitis . Thus, this article aims to analyze the epidemiological profile of inflammatory bowel disease due to hospitalization in the Northeast region from 2013 to 2023. Methodology: a descriptive cross-sectional epidemiological study was carried out based on the SUS health information department (DATA/SUS) using the variables: hospital admissions, mortality rate, deaths, age group, color/race, sex, type of care and health macro-region, average hospital stay. Results: 1185600 hospitalizations occurred during the studied period, with the southeast region being most affected in relation to the number of hospitalizations, and the north region least affected. In line with the region with the most hospitalizations, the southeast region also presented the highest value of expenses and deaths in relation to IBD. Conclusion: the importance of already published studies is highlighted and the need to encourage their expansion, in order to promote a more comprehensive discussion on prophylaxis measures and implementation of appropriate early treatment to improve the quality of life of patients affected by this pathology.